Cyber Crime Law Enforcement Against Illegal Access to Online Banking in Indonesia - Mohamad Yusuf; Tofik Yanuar Chandra; Ramlani Lina Sinaulan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Cybercrime refers to the activity of a crime with a computer or computer network being a tool, target or place where a crime occurs. These include online auctions, cheque forgery, credit card fraud, identity fraud and child pornography and illegal internet access. The development of technology and its application has infiltrated and strongly influenced modern life, even a largeparagraph of business activities has entrusted to such technology, one of which is the banking industry. The purpose of the research in this paper is to analyze cyber crime law enforcement against illegal access to online banking in Indonesia and analyze the punishment of perpetrators of illegal access to online banking in Indonesia. The research uses a normative juridical approach that emphasizes literature research. In this study, what is used is the Statutory approach, the conceptual approach, the differential approach, the case approach, and the historical approach. The sources of Legal Materials used are primary, secondary and tertiary legal materials. The analysis of the legal materials used is qualitative.  Based on research, it shows that the law enforcement used as the legal basis for cybercrime cases is Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE). With the ITE law, it is hoped that it can protect the public of information technology users in Indonesia. This is important considering the increasing number of internet technology users from year to year. The increasing use of the internet on the one hand provides many conveniences for humans in carrying out their activities, on the other hand making it easier for certain parties to commit criminal acts.